Science in itself and science in us: on the role of the epist?m? in the Phaedrus - García, Gabriel (2022)
The view of the ????? ???????????? in the Phaedrus is described according to three contents: justice (??????????), soundness (?????????) and science (????????). Only the latter is specified (247d6-e2). In „‘Der Geistcharakter des Überhimmlischen Raumes‘. Zur Korrektur der herrschenden Auffassung von Phaidros 247c-e”, W. Schwabe argued that this passage necessarily distinguishes the science “in what is” from the science “in what we now call beings”, and that the latter refers to science as a human practice of acquiring and transmitting knowledge. After reviewing his main arguments, I will examine this distinction in the whole dialogue, especially regarding the science “in what we now call beings”, in two moments: 1) the accurate description of the vision of science as memory, ?????, when the soul returns to the sensible realm, as well as its recovery in the erotic relation (both themes of the palinode) and 2) the relation between memory and science in the transmission of knowledge, in the critique of writing. The identification of science with the “immortal seed” contained in the dialectician’s speeches (276 e5-277 a4) will be linked to the analysis of procreation in beauty in the Symposion, showing that the ???????? as content of the ????? expresses the dynamic relation between ideas. Therefore, the difference between “science in itself” and “science in us” must be conceived as a “structural feature” of the eidetic realm, in the same way as justice in the Republic (500c3-4) and, presumably, soundness.